Gene expression and single nucleotide polymorphism (rs 1042838) of progesterone receptor gene in Iraqi females with recurrent spontaneous abortion(RSA) - Farhan, Shireen Hamid; Abdul-Hassan, Ismail A.; Abdul-Rahman , Ruoida (International Journal of Psychosocial Rehabilitation, 2020)
The proposal target was determining the gene expression and single nucleotide polymorphism (rs1042838 G>T) of progesterone receptor gene in blood sample of recurrent spontaneous abortion RSA Iraqi females. Fifty females (n=50) with RSA consulted Al-Elwiya teaching hospital from February to June 2019 and apparently healthy fertile control (n=50) were enrolled. Following the serum hormonal assay, DNA and RNA were extracted from leucocytes to detriment the SNP and gene expression were carried out by (RT-q PCR). The results showed significant disruption of hormones between the two groups and non -significant difference (p>0.05) in the mean of threshold cycle(ΔCt) of progesterone receptor gene between female with RSA and control. Assessing the 2־ΔΔCt in female with RSA showed non -significant increased expression of folding in progesterone receptor m RNA compared with control. The genotypes and allele frequencies in the two groups showed significant decrease in the mutant (TT) genotype frequency in female with RSA. In conclusion, up-regulation of progesterone receptor gene expression was observed in female with RSA, the mutant genotype may play as protective SNP against RSA.